Performance Validation Of Nasa-Power Data For Drought Monitoring In The Kelantan River Basin, Malaysia - Rosli, Lily Suhana Mohamed (2024)
The national aeronautics and space administration prediction of worldwide energy resources (nasa-power) offers long-term meteorological data to support the renewable energy and agricultural sectors. While nasa-power provides an alternative open-source climate data, its effectiveness for drought monitoring in tropical regions is still unclear in the literature. Therefore, this study aims to evaluate the capability of nasa-power in estimating precipitation and droughts from 1985 to 2020 in the kelantan river basin (krb), malaysia. To analyse different drought patterns, the standardized precipitation index (spi) and standardized streamflow index (ssi) were applied at 1-, 3-, 6-, and 12-month time scales. In addition, the mann-kendall test was utilized to measure trends, whereas the sens slope was used to evaluate changes in drought magnitude. Spearman's rho was utilized to explore the relationship between droughts and major atmospheric circulations like el niño-southern oscillation (enso), indian ocean dipole (iod), and madden-julian oscillation (mjo). The findings indicate that nasa-power generally performed satisfactorily in estimating precipitation and temperature across all time scales, particularly on a monthly basis and in northern coastal areas. However, it tended to underestimate minimum and maximum temperatures, as well as precipitation.